2014
DOI: 10.1103/physreva.89.023839
|View full text |Cite
|
Sign up to set email alerts
|

Low-light-level four-wave mixing by quantum interference

Abstract: We observed electromagnetically-induced-transparency-based four-wave mixing (FWM) in the pulsed regime at low light levels. The FWM conversion efficiency of 3.8(9)% was observed in a four-level system of cold 87Rb atoms using a driving laser pulse with a peak intensity of approximately 80 {\mu}W/cm^2, corresponding to an energy of approximately 60 photons per atomic cross section. Comparison between the experimental data and the theoretical predictions proposed by Harris and Hau [Phys. Rev. Lett. 82, 4611 (199… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…According to equation (6), an OD of 250 enables the conversion efficiency of B96%. The same efficiency requires an OD of 500 in the widely used double-L scheme 55 . Hence, the DT scheme is a new and advantageous method of nonlinear frequency conversion.…”
Section: Resultsmentioning
confidence: 99%
“…According to equation (6), an OD of 250 enables the conversion efficiency of B96%. The same efficiency requires an OD of 500 in the widely used double-L scheme 55 . Hence, the DT scheme is a new and advantageous method of nonlinear frequency conversion.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first observation of a CE exceeding 25% in the resonant double-Λ EIT scheme. According to the theoretical model, this resonant backward scheme can achieve 96% CE by using a medium with a large OD of 200, which reaches the same CE as the previous non-resonant scheme at half the OD 34 . Moreover, to compare the experimental data with the theoretical predictions, the phase-mismatch effect is included in the theoretical model, which was not considered in an earlier study of backward FWM 35 .…”
Section: Introductionmentioning
confidence: 77%
“…A simple method of suppressing spontaneous emission and thereby increasing the FWM efficiency in this forward double-Λ scheme is to shift the frequency of the applied laser field away from the resonant transition. Even though the interaction strength between light and matter is decreased in the non-resonant case, two research teams have demonstrated that the FWM efficiency can overcome the conversion limit (25%) of the resonant case 33 , 34 . Herein, we demonstrate that spontaneous emission can be effectively suppressed under a resonant condition only by arranging the applied laser beams in a backward configuration, which is the so-called backward FWM that was theoretically studied by Kang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The experimental data 11 NOVEMBER 2016 also show that the power of the transmitted light exceeds its input power in the double-Λ system. This light-amplification phenomenon is caused by the coherent light transfer between two N-type fourwave-mixing processes (j1i → j3i → j2i → j4i → j1i and j1i → j4i → j2i → j3i → j1i) [37]. More detailed discussions on the coherent light amplification can be found in the Supplemental Material [38].…”
Section: (B)mentioning
confidence: 99%